ISLAM AND RELIGIOUS EXPERIENCE IN THE POSTMODERN - Sidqi, Ahmad (Jurnal Filsafat "WISDOM", 2017)
The Islamic experience in the modern world reconstitutes the relation between human and God on the basis of the fundamental authority of the holy Quran. Mosque as a symbol, this monument to political power contains some of the most basic contradictions thats characterize Muslim societies inÂ the modern world. A similar distinction applies to the to the morning officialy attributed to the mosque, it maybe â€œopenâ€, â€œtoleranâ€, â€œcosmopolitanâ€, and â€œmodernâ€ Muslim reformers, embattled governments against increasingly militant oppositional groups which have adopted Islam as an overarching instrument of discourse and struggle. Muslim reformers, activists, and militants nearly always say that theirs is a â€œmovementâ€, a â€˜currentâ€ which is still in the process of gestation and evolution. Emancipatory politics is concerned, above all, with themes of justice, equality, and participation, the very same themes that most Muslim reformers are in fact concerned with. Islamic experience involves a redefination of identity in a world which has become homogenized by the globalizing process of modernism The Islamic experience is therefore a call for an emancipatory politics which means justice where there is none, a more egalitarian distribution of wealth and a more democratic system of decision making.Â